2015
DOI: 10.1586/1744666x.2015.1083861
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding xenotransplantation: implications for the clinic

Abstract: Summary The results of organ and cell allotransplantation continue to improve, but the field remains limited by a lack of deceased donor organs. Xenotransplantation, e.g., between pig and human, offers unlimited organs and cells for clinical transplantation. The immune barriers include a strong innate immune response in addition to the adaptive T cell response. The innate response has largely been overcome by the transplantation of organs from pigs with genetic modifications that protect their tissues from thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 101 publications
(108 reference statements)
0
33
0
4
Order By: Relevance
“…Recent studies have demonstrated that hCD47 expression in pigs is one of the solutions to overcome acute rejection caused by macrophagemediated rejection. 20 It has been reported that hCD47-expressing α1,3-galactosyltransferase knockout pigs are promising solutions for xenotransplantation. 21 In this study, hCD47-expressing PK15 cells showed better viability when exposed to activated THP-1 cells than wild-type PK-15 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that hCD47 expression in pigs is one of the solutions to overcome acute rejection caused by macrophagemediated rejection. 20 It has been reported that hCD47-expressing α1,3-galactosyltransferase knockout pigs are promising solutions for xenotransplantation. 21 In this study, hCD47-expressing PK15 cells showed better viability when exposed to activated THP-1 cells than wild-type PK-15 cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reasons that pigs would be an ideal source for liver xenotransplantation (LXT), especially when compared to other potential donors such as non-human primates (NHPs). (7) Namely, they have good breeding potential, rapid growth, adequate adult organ size, relatively low cost of maintenance, and close anatomic and physiology similarity to humans. (7) Additionally, considerable knowledge and experience has been gained over the years with regards to tissue typing and genetic engineering making their potential to be optimal donors more likely.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Namely, they have good breeding potential, rapid growth, adequate adult organ size, relatively low cost of maintenance, and close anatomic and physiology similarity to humans. (7) Additionally, considerable knowledge and experience has been gained over the years with regards to tissue typing and genetic engineering making their potential to be optimal donors more likely. (7) Until recently, challenges related to the consistent development of lethal coagulopathy has troubled progress in the field of pig-to-NHP LXT, however, reports suggesting prolonged survival of nearly a month have reinvigorated interest (FIGURE 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports of liver xenotransplantation between species of NHPs [reviewed in 242 ], but, for a number of reasons, 9 it is very unlikely that NHPs will be acceptable as sources of livers for clinical transplantation in the future. The pig-to-NHP model is increasingly being investigated to assess strategies aimed at advancing towards clinical xenotransplantation (Figure 1).…”
Section: Introductionmentioning
confidence: 99%